Pengaruh Media Sosial, Kualitas Produk dan Harga terhadap Keputusan Pembelian Somethinc di Sidoarjo - Sabilla, Shafa Shal; Febriansyah, Rizky Eka; Sumartik, Sumartik (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of social media, product quality and price on purchasing decisions for Somethingnc in Sidoarjo. This research uses quantitative methods, sampling using purposive sampling. Respondents numbered 100 participants and used a questionnaire, then the data was analyzed using SPSS. The results of this research reveal that simultaneously and partially there is a significant influence between social media variables, product quality and price on the decision to purchase Somethingnc in Sidoarjo.